1999
DOI: 10.1111/j.1740-8261.1999.tb02131.x
|View full text |Cite
|
Sign up to set email alerts
|

UROCYSTOLITH DETECTION: COMPARISON OF SURVEY, CONTRAST RADIOGRAPHIC AND ULTRASONOGRAPHIC TECHNIQUES IN ANIN VITROBLADDER PHANTOM

Abstract: Urocystoliths of 9 mineral types from 437 canine patients submitted to the University of Minnesota Urolith Bank were imaged in a urinary bladder phantom. Imaging techniques simulated were survey radiography, pneumocystography, double contrast cystography (two iodine concentrations) and real-time ultrasonography (3.5 MHz, 5.0 MHz, 7.5 MHz). Imaging techniques were compared for accuracy of urocystolith detection, accuracy of urocystolith enumeration, and tendencies for over or undercounting. Across urocystolith … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
1
31
1
Order By: Relevance
“…On ultrasonographic images, however, the bladder phantom wall appeared to be more hyperechoic than the normal canine bladder. 19 Although artifacts were present in most ultrasonographic images in the present study, they appeared to be less extensive than those reported in a previous in vitro study, 7,8 largely because of the absence of metal bolts within the phantom. A similar flattened appearance was observed in a previous in vitro study 8 in which a lower-frequency transducer (3.5 to 7.5 MHz) was used.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…On ultrasonographic images, however, the bladder phantom wall appeared to be more hyperechoic than the normal canine bladder. 19 Although artifacts were present in most ultrasonographic images in the present study, they appeared to be less extensive than those reported in a previous in vitro study, 7,8 largely because of the absence of metal bolts within the phantom. A similar flattened appearance was observed in a previous in vitro study 8 in which a lower-frequency transducer (3.5 to 7.5 MHz) was used.…”
Section: Discussioncontrasting
confidence: 68%
“…[7][8][9][10][11] Overall, the quality of images obtained by computed tomography, radiography, and cystography was excellent and comparable to the quality of images obtained in vivo. Despite these potential disadvantages, in vitro phantoms are well suited for imaging and have been used to evaluate the diagnostic performance of various imaging modalities for detection of cystoliths.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations